Aluminum Waste as Electrode for Home Textile Industry Wastewater Treatment using Batch Electrocoagulation Process: Studies on Operating Parameters - Irawan, Chairul; Mu'minah, Ridhayanti; Purnawilda, Agita; Fatyasari Nata, Iryanti (Jurnal Sains Materi Indonesia, 2024)
The manufacture of the Sasirangan home textile industry involves coloring and dyeing processes using synthetic dyes in large quantities. These contaminants of dyes and organic materials would cause high color and chemical oxygen demand (COD) contaminants values. This study aims to characterize the wastewater of batik-modified Sasirangan and determine the effect of current density and length of operating time on color removal and reduction of COD in Sasirangan home textile industry wastewater through the batch electrocoagulation process. The method used in this research is an electric current flowing in the same direction to the Sasirangan home textile industry wastewater in a reactor with dimensions of 310  180  240 mm3. The electrode used is aluminum alloy type 1100. The aluminum/aluminum (Al/Al) electrode is used in this electrocoagulation (EC) process, then connected to a direct current (DC) power supply. The experiment was carried out at room temperature using an electrode distance of 2 cm with variations in the time of the electrocoagulation process for 15–120 minutes. The experiment was repeated for variations in pH (4–9) with a current density of 3.5–5.5 mA/cm2. Furthermore, an analysis of the color removal and the decrease in the concentration of COD was carried out. The results showed that the contaminant content in Sasirangan home textile industry wastewater decreased significantly, whereas the optimal conditions for the EC reaction were determined using color and COD removal efficiency parameters. The decrease in color and COD concentrations occurred at a current density of 5.5 mA/cm2 with a pH of 4 for 120 minutes, around 1110 PtCo and 90.4 mg/L of COD, respectively